Implementation Approach Inquiry in Science learning for Increase Ability Think Critical - Ningsih, Dewi Andariya (Scientica Education Journal, 2025)
This study aims to analyze the effectiveness of the inquiry approach in science learning to improve the critical thinking skills of junior high school students in Indonesia. The research employed a quasi-experimental method using a pretest-posttest control group design. A total of 120 students were selected and divided into two groups: an experimental group (taught using the inquiry approach) and a control group (taught using conventional methods). The instrument used to measure critical thinking was developed based on Ennis's indicators and adapted to the Indonesian context. The analysis revealed a significant difference between the experimental and control groups, with an effect size of 3.75, indicating a substantial practical impact of the inquiry approach on students' critical thinking development. Each critical thinking component including interpretation, analysis, evaluation, inference, and explanation showed a significant improvement. The study also highlights that integrating local cultural contexts into inquiry-based learning enhances its relevance and effectiveness. These findings support the implementation of inquiry-based approaches as a more effective alternative to conventional teaching methods in fostering students' critical thinking skills in Indonesian science education